Comparative Analysis of Meteorological Drought based on the SPI and SPEI Indices - Cheikh Faye (HighTech and Innovation Journal, 2022)
The management of water resources in our states has become increasingly difficult in recent times due to the frequency and intensity of droughts. In the context of climate change, extreme weather and climate phenomena such as floods and droughts that are increasingly occurring have adverse consequences on the socio-economic development of the Senegalese territory. Droughts that affect water availability, agricultural production, and livestock operations are generally identified and characterized using drought indices. The objective of this paper is to analyze the hydrological drought trend in two Senegalese regions, the Senegal River valley and the Casamance basin, with different climatic characteristics (Sahelian continental climate and South Sudanian tropical climate, respectively) during the period 1981-2017. For this purpose, daily data from uniformly installed 8 meteorological stations in the two areas were examined, and trends in the standardized precipitation index (SPI) and standardized precipitation-evapotranspiration index (SPEI) were also assessed. The similarities and differences between the indices of the two regions were then examined. In most stations in both areas, there is a statistically significant trend of increasing SPI and SPEI (75% of the stations for SPI and 87.5% for SPEI), despite some negative trends (e.g., SPI in Bakel, SPE and SPEI in Matam, SPEI in Saint Louis). Moreover, the trend of the indices averaged over the stations of the two indices, although generally positive in the two climatic zones considered (with the exception of the SPI in the valley where it is negative), is only significant in the Casamance basin zone.